Apical Sealing Ability of a Novel Material: Analysis by Fluid Filtration Technique - Gizem Ozbay; Burak Kitiki; Sertac Peker; Betul Kargul (University of Zagreb. School of Dental Medicine, 2014)
Aim: The aim of this study is to evaluate the sealing ability of BiodentineTM, which is new calcium-silicate based dental cement and has endodontic indications similar to those of MTA. Methods: The study sample consists of 21extracted human mandibular anterior teeth. The teeth were submitted to root-end preparation and instrumented up to file #40 by step back technique and randomly divided into 3 study groups (n=7): White MTA AngelusTM (Angelus, Angelus Odontológica, Londrina, PR, Brazil), BiodentineTM (Septodont, SeptodontSpecialités, Saint-MaurdesFosses, France) and the controls. The length of dye penetration between the filling material and tooth structure was measured in millimetres, using a calibrated stereo microscope (Leica MZ75, Germany) at 20× magnification under the same conditions. One-way Analysis of Variance (ANOVA) was used to indicate differences between the experimental groups and the controls. In addition, Tukey Multiple Comparisons Test was used to indicate differences within each group. Results: The results showed that none of the groups were completely sealed. The mean and standard deviation for dye penetration in BiodentineTM group was 0.63±0.20 and in MTA AngelusTM group, it was 0.26±0.25. Regarding the comparisons between each group, significant differences were not observed (P=0.0193). The comparison between materials only found a significant difference only between MTA AngelusTM and BiodentineTM (P<0.05). Conclusions: This study evaluated the possibility of BiodentineTM's sealing ability and marginal adaptation, since no studies are available on iodentine. However, further in vitro and in vivo investigations should be conducted to determine the suitability of BiodentineTM for clinical application.